2014
DOI: 10.29079/vol13iss2art297
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bovine rotavirus in diarrheic calves by using rapid test in some Mid-Euphrates provinces

Abstract: The study was aimed to determine the Rota viral infection rates in diarrheic calves and effectiveness of some epidemiological factors on that rate in some provinces in Mid-Euphrates region in Iraq (Babylon, Al-Najaf, Karbala, Al-Qadisyia provinces). A total of 530 calves aged between 1-60 day were examined and fifty fecal (50) samples were collected from diarrheic calves only within six months period from November-2012 to April -2013. The fecal samples were examined for the presence of rotavirus by rapid rotav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
1
1
Order By: Relevance
“…The present results demonstrated (38%) and (30%) of Rotavirus infection in Karbala and Basrah provinces respectively (Table 3). This result was compatible with study of (19) found there is no significant variances between Male and female (37.5%, 40% respectively) were seen diseased. While (20) found range prevalence or Rotavirus A by using chromatographic immunoassay (Monoclonal antibodies) to capture the attendance of rotavirus virus antigen with 71% (85 of 119 samples) were highest positive in Wasit province, but the lowest positive was in Dyala province 15% (4 of 26 samples) in middle provinces regions of Iraq from cattle and buffalo calf with acute diarrhea.…”
Section: Rotavirus Prevalence In Bovine Fecal Samples By Imunochromotsupporting
confidence: 92%
“…The present results demonstrated (38%) and (30%) of Rotavirus infection in Karbala and Basrah provinces respectively (Table 3). This result was compatible with study of (19) found there is no significant variances between Male and female (37.5%, 40% respectively) were seen diseased. While (20) found range prevalence or Rotavirus A by using chromatographic immunoassay (Monoclonal antibodies) to capture the attendance of rotavirus virus antigen with 71% (85 of 119 samples) were highest positive in Wasit province, but the lowest positive was in Dyala province 15% (4 of 26 samples) in middle provinces regions of Iraq from cattle and buffalo calf with acute diarrhea.…”
Section: Rotavirus Prevalence In Bovine Fecal Samples By Imunochromotsupporting
confidence: 92%
“…Remarkably, the prevalence of this viral infection was found to be much higher in other countries compared to our study, e.g. 63% in Argentina [4], 79.9% in Australia [33], 32.5% in Sudan [34] and 36% in Iraq [35]. Different spatial, temporal and management-related factors might influence the prevalence of BRV infection.…”
Section: Epidemiology Of Bovine Rotaviruscontrasting
confidence: 56%
“…A previous study by using rapid test on calve fecal samples showed in Babylon, Karbala ,Najaf, AL-Qadisyia revealed that infection rate were 60%, 20% , 40% and 33% respectively (10). Chromatographic Immunoassay and ELISA are the simple and good standard methods for detection of rotavirus.…”
Section: Resultsmentioning
confidence: 99%